Fifty Years of Prefrontal Cortex Research: Impact on Assessment. (4th December 2017) - Burgess, Paul W.; Stuss, Donald T.
Abstract: Our knowledge of the functions of the prefrontal cortex, often called executive, supervisory, or control, has been transformed over the past 50 years. After operationally defining terms for clarification, we review the impact of advances in functional, structural, and theoretical levels of understanding upon neuropsychological assessment practice as a means of identifying 11 principles/challenges relating to assessment of executive function. Three of these were already known 50 years ago, and 8 have been confirmed or emerged since. Key themes over this period have been the emergence of the use of naturalistic tests to address issues of "ecological validity"; discovery of the complexity of the frontal lobe control system; invention of new tests for clinical use; development of key theoretical frameworks that address the issue of the role of prefrontal cortex systems in the organization of human cognition; the move toward considering brain systems rather than brain regions; the advent of functional neuroimaging, and its emerging integration into clinical practice. Despite these huge advances, however, practicing neuropsychologists are still desperately in need of new ways of measuring executive function. We discuss pathways by which this might happen, including decoupling the two levels of explanation (information processing; brain structure) and integrating very recent technological advances into the neuropsychologist's toolbox. ( JINS, 2017, 23, 755–767)